Karakteristik Komposit Bioplastik Dalam Variasi Rasio Pati Umbi Talas (Xanthosoma sagittifolium)-Kitosan (Jurnal Ilmiah Teknologi Pertanian Agrotechno, 2020)
This research aims to know the effect of variations in the ratio of taro-chitosan tuber starch to the characteristics of bioplastic composites and determine the ratio of taro-chitosan tuber starch that produces the best bioplastic composites. This research uses a Factorial Randomized Block design with taro-chitosan tuber starch ratio variation factor in  five level (40: 60%, 35: 65%, 30: 70%, 25: 75% and 20: 80%). The treatments which grouped into 3 based on the time of making bioplastics, so there are 15 experimental units. The observed variables which tensile strength, elongation at break, modulus young, swelling development, biodegradation and FTIR test. The obtained data were analyzed for diversity and continued with the Honestly Significant Difference test. The results showed that the variation of the taro-chitosan tuber starch ratio significantly affected the tensile strength, elongation at break, modulus young, and swelling development but did not significantly affected the biodegradation of the bioplastic composites of taro-chitosan tuber starch. Variation of taro-chitosan tuber starch ratio 35: 65% produces the best bioplastic composite characteristics with tensile strength values 3.15 MPa, elongation at break 21.33%, modulus young of 14.87 MPa, swelling development test 29.69% and biodagradation ability for 13 days. FTIR analysis results show the presence of hydroxyl (O-H) alcoholic groups, (O-H) Carboxylic acid, (C = O) esters, (C - H) alkana,  (C=C) alkena , and hydrocarbons - (CH2) n.
Keywords: Komposit bioplastik; variasi rasio; umbi talas; kitosan; gliserol